(untitled) (Bangladesh Journal of Botany, 2024)
The current study aimed to develop an effective micropropagation protocol for Bambusa vulgaris var. striata, through direct organogenesis using nodal explant. The maximum axillary bud break (84%) with the greatest number of shoots per explant (5.20 ± 0.37) was achieved using liquid MS medium containing 2.5 mg/l BAP and 1.5 mg/l TDZ, while the maximum length of shoots (7.12 ± 0.27 cm) was induced on 2.0 mg/l BAP. Shoots were multiplied in stirred liquid MS medium with 3.0 mg/l BAP, resulting in the highest number of shoots per culture (13.20 ± 0.58) with the shoot length of 7.32 ± 0.48 cm. BAP in combination with TDZ resulted in a feeble response to shoot proliferation; although in some cases, the presence of TDZ with BAP was inhibitory. The shoots progressively increased in number and length over the first four subculture cycles in the aforementioned medium, but declined in the 5th sub-culture cycle. Following the 4th sub-culture cycle, each culture produced 16.60 ± 0.60 shoots with an average length of 8.96 ± 0.61 cm. Adding 10% coconut water to the medium resulted in excellent shoot growth and development, with an average of 18.40 ± 1.44 shoots per culture, measuring 8.56 ± 0.79 cm. Half-strength MS medium with 3.0 mg/l IBA resulted in the highest rooting percentage (85%) and the most roots per culture (8.00 ± 0.71). Successful acclimatization of well-rooted clumps of 3-4 shoots was achieved in a mixture of soil, sand, and compost (2:1:1) with 85% survival rate. Bangladesh J. Bot. 53(4): 939-947, 2024 (December)